SYNERGISTIC EFFECT OF SPINOSAD WITH SELECTED BOTANICAL POWDERS AS BIO-RATIONAL INSECTICIDE AGAINST ADULT TRIBOLIUM CASTANEUM HERBST (COLEOPTERA: TENEBRONIDAE) - Babarinde, Samuel Adelani; Kemabonta, Kehinde Abike; Aderanti, Ifeoluwa Adedamola; Kolawole, Funmilayo Christianah; Adeleye, Adetayo David (Journal of Agricultural Sciences (Belgrade), 2018)
Synergistic effect of spinosad with three botanical (Aframomum melegueta, Eugenia aromatica and Piper guineense) powders were investigated as biorational insecticides against Tribolium castaneum Herbst (Coleoptera: Tenebrionidae) infesting melon (Citrullus lanatus) seed. Treatments included sole application of each botanical (50 g/ kg melon seed), sole application of spinosad (SASp) (1.0 g/ kg), mixture of spinosad (0.5 g/kg) + botanical powders (25 g/kg) and an untreated control. Data were collected on tenebronid mortality rate (%) (PM) and melon seed weight loss rate in % (PWL). Phytochemical analysis of the botanicals was also carried out. At 3 -14 days after treatment (DAT), PM observed in melon seeds treated with SASp (90.00-100.00%) was not significantly (p>0.05) different from PM observed in melon treated with spinosad + E. aromatica powder (86.67-100.00%) and spinosad + P. guineense powder (85.00-100.00%). PWL observed in melon seeds treated with spinosad + botanical powders (1.17-1.40%) was not significantly different from PWL observed in seeds treated with SASp (0.42%), but significantly lower than PWL (3.28%) observed in melon seed treated with sole application of A. melegueta powder. P. guineense powder had the highest alkaloid (868.33 mg/100 g), tannins (550.00 mg/100 g), phenolics (53.57 GAE/g), and steroids (740.00 mg/100 g), E. aromatica had the highest flavonoids (1466.67 mg/100 g), terpenoids (1276 mg/100 g) and cardiac glycosides (7.33 mg/100 g), while A. melegueta had the highest saponins (376.67 mg/100 g). Combination of spinosad with P. guineense or E. aromatica powder performed better than combination with A. melegueta and is therefore recommended as a biorational approach for the control of T. castaneum..
Keywords: red flour beetle; spinosad; seeds; synergistic effect; Melons; Botanical powder